G129(P) The effect of individualised care on maternal anxiety and depression. (27th April 2015) - Shah, P; Roth, S
Abstract : Aims: The introduction of individualised care rooms (ICR) at Barnet Hospital has allowed family-centred neonatal care to take place in an environment where the mother is empowered as the main carer for her newborn with the support of trained staff. This study aims to quantify the effect this has on maternal mood in the postnatal period. Methods: Mothers of babies that had either been in the special care baby unit (SCBU) or ICR for 3 or more days were asked to complete the Edinburgh Postnatal Depression Questionnaire. The questionnaire is scored out of 30, with a higher score representing more severe concerns regarding maternal mood. Results: Questionnaires were handed out to 10 parents in each of the 2 groups. They were returned by 7 parents from ICR and 8 parents from SCBU. The average length of stay was 18 days in the ICR group and 24 days in the SCBU group. The mean score was 4.57 in the ICR group, compared to 10.37 in the SCBU group with a p value of 0.04. Conclusion: This study highlights how important maternal involvement and empowerment can be in neonatal care. Improvements in maternal mood will aid bonding and have a positive effect on the emotional and social development of the child and the family unit.